Body mass index and the risk of ulnar nerve entrapment in individuals without diabetes-a longitudinal cohort study from Sweden - Rydberg, Mattias ; 0000-0002-8249-8660; Dahlin, Lars B ; 0000-0003-1334-3099; Nilsson, Peter M; Zimmerman, Malin ; 0000-0002-9925-3838 (International Journal of Obesity, 2025)
INTRODUCTION: Ulnar nerve entrapment (UNE) is a common disorder with many associated risk factors. Diabetes mellitus (DM) is an established risk factor, but less is known about metabolic risk factors in individuals without diabetes. Our study aimed to explore the association of body mass index (BMI) with UNE during long-term follow-up. METHOD: The population-based cohort study Malmö Diet and Cancer Study (MDCS) and the Swedish Patient Register (NPR) were cross-linked. Between 1991 and 1996, 30,446 subjects were recruited to MDCS and were followed to a diagnosis of UNE, emigration, death, or end of study on December 31, 2020. BMI at study entry was stratified into normal weight (<25), overweight (25-30) and obesity (>30). To omit the effect of DM, individuals with prevalent or incident DM were excluded. To calculate the association between BMI and incident UNE, Cox proportional hazard models adjusted for age, sex, hypertension, smoking, manual work, and alcohol consumption were used. RESULTS: A total of 23,254 individuals were followed for over 25 years, whereof 192 (0.8%) developed UNE. In the multivariable Cox regression models, BMI was independently associated with UNE (HR 1.07; 95% CI 1.03-1.11, p < 0.001). Both overweight (HR 1.55; 95% CI 1.12-2.15, p < 0.01) and obesity (HR 2.23; 95% CI 1.40-3.57, p = 0.001) were associated with an increased risk compared to individuals with normal weight. CONCLUSION: High BMI is associated with the development of UNE in individuals without diabetes, indicating that high BMI is an independent risk factor for the development of nerve entrapment disorders irrespective of hyperglycaemia.
© 2025. The Author(s).